2009
DOI: 10.1901/jaba.2009.42-511
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Prefer Contingencies? An Evaluation of the Efficacy of and Preference for Contingent Versus Noncontingent Social Reinforcement During Play

Abstract: Discovering whether children prefer reinforcement via a contingency or independent of their behavior is important considering the ubiquity of these programmed schedules of reinforcement. The current study evaluated the efficacy of and preference for social interaction within differential reinforcement of alternative behavior (DRA) and noncontingent reinforcement (NCR) schedules with typically developing children. Results showed that 7 of the 8 children preferred the DRA schedule; 1 child was indifferent. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 17 publications
4
87
1
Order By: Relevance
“…As an aside, this preference for contingent over noncontingent reinforcement also has some generality. Luczynski and Hanley (2009) recently showed that 7 of 8 children of typical development preferred contingent to noncontingent social reinforcement using the same assessment procedures (one child was indifferent).…”
Section: Single-person Applicationsmentioning
confidence: 99%
“…As an aside, this preference for contingent over noncontingent reinforcement also has some generality. Luczynski and Hanley (2009) recently showed that 7 of 8 children of typical development preferred contingent to noncontingent social reinforcement using the same assessment procedures (one child was indifferent).…”
Section: Single-person Applicationsmentioning
confidence: 99%
“…A growing number of studies (e.g., Hanley, Piazza, Fisher, Contrucci, & Maglieri, 1997;Luczynski & Hanley, 2009 have indicated that individuals prefer contingency-based treatments over time-based treatments. Assessing preference within the context of treatments for challenging behavior maintained by the termination of interruptions of ongoing activities exhibited by individuals with ASD might lead to selections by clinicians of more effective available treatments.…”
Section: Discussionmentioning
confidence: 99%
“…blocking, restraint) which are designed to mitigate, obstruct, or prevent responding. Giving individuals the choice to engage in some response (and contact reinforcement through a contingency) is typically more preferred than interventions that do not (Luczynski and Hanley 2009), which could have implications for the course of treatment for pica. Recently, Slocum et al (2017) used a differential reinforcement procedure to teach a 13-year-old girl with autism spectrum disorder to engage in a discard response, which consisted of picking up and putting pica items in a nearby trashcan.…”
mentioning
confidence: 99%